ENVIRONMENTAL EDUCATION IN PERSPECTIVE: FIELD CLASS AS A PEDAGOGICAL TOOL IN TEACHING ECOLOGY AND THE ENVIRONMENT: A DIDACTIC PROPOSAL INTEGRATED WITH THE BNCC - dos Santos, Alan Christian Moreira; Scabio, Aline Cristina Moreira; do Nascimento Brum de Souza, Bruna Alexia; dos Santos, João Vitor Moreira Martins (Seven Editora, 2025)
This work proposes to promote learning about ecology, biodiversity, soil formation and use, the importance of aerial rivers and carbon sequestration, mechanisms for reducing global temperature rise, and environmental preservation through ecological trails in an area of extreme environmental importance in the municipality of Vila Velha, in the Lagoa Encantada Permanent Preservation Area (APP Lagoa Encantada), thus connecting theory and practice in a meaningful way. This involved conducting a field trip in an area of extreme environmental importance in the municipality of Vila Velha. Pre- and post-field activities were conducted to consolidate the acquired knowledge, encourage critical reflection on environmental conservation among 6th and 7th grade elementary school students, and finally, create a pedagogical activity plan that can be replicated in other schools in the region. During practical activities on the ecological trails, students apply the concepts, observing and recording local fauna and flora, analyzing food chains, and assessing the region’s environmental impacts. After the field activities, supplementary activities were held, such as a field lesson report and questionnaire, discussion groups, and other activities. Students were able to develop various skills and abilities from the National Common Curriculum Base (BNCC). DOI: https://doi.org/10.56238/sevened2025.030-038